1993
DOI: 10.1136/adc.68.1_spec_no.35
|View full text |Cite
|
Sign up to set email alerts
|

Fetal anaemia and its relation with increased concentrations of adenosine.

Abstract: Adenosine concentrations were measured in umbilical venous blood obtained by cordocentesis from 14 fetuses of 19-34 weeks' gestation. The concentration did not change significantly with gestational age, but anaemic fetuses showed significantly increased concentrations of adenosine and there was a positive association with blood oxygen tension. These findings suggest that the fetus responds to tissue hypoxia by increasing blood adenosine concentrations from at least 19 weeks' gestation. (Arch Dis Child 1993;68:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A previous study demonstrated that the plasma [ADO] increases in anemic patients [8]. In this study, a slight decrease of the RBC count, hematocrit and hemoglobin concentration was observed.…”
Section: Discussionmentioning
confidence: 59%
“…A previous study demonstrated that the plasma [ADO] increases in anemic patients [8]. In this study, a slight decrease of the RBC count, hematocrit and hemoglobin concentration was observed.…”
Section: Discussionmentioning
confidence: 59%
“…LPS upregulates ecto-59-nucleotidase activity on HUVECs, and it was suggested that because adenosine is an anti-inflammatory molecule, 59-nucleotidase upregulation may protect endothelial cells against inflammatory damage (Li et al, 2008b). Adenosine concentration in umbilical venous blood increased significantly in anemic fetuses, suggesting that the fetus responds to hypoxia by increasing blood adenosine (Ross Russell et al, 1993). Functional A 1 and A 2B receptors were shown to be expressed on the HUVEC-derived ECV304 cell line .…”
Section: N Human Umbilical and Placental Vesselsmentioning
confidence: 99%
“…Adenosine and ATP have also been implicated. Adenosine is released from the placenta into umbilical venous blood in anemia, hypoxia, growth retardation and pre-eclampsia [4–6] . Moreover, hypoxia decreases adenosine uptake via its endonucleoside transporter (ENT-1) in human umbilical vein endothelial cells (HUVEC) [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Further, the balance of ATP, ADP and adenosine regulate platelet aggregation, inflammation, immunity, and vascular proliferation, high concentrations of ATP being pro-inflammatory and immunostimulatory [5,10–12] . It has been reported that ATP is released from endothelial cells by hypoxia [1,4,5] . However, whilst hypoxia augmented shear stress-stimulated ATP release from primary HUVEC, hypoxia alone did not affect ATP release [13] .…”
Section: Introductionmentioning
confidence: 99%